Digital Board Game: Is there a need for it in language learning among tertiary level students? - Zuraina, Ali; Mohd Amir Izzudin, Mohamad Ghazali; Rosnani, Ismail; Nurul Nadia, Muhammad; Noor Azlinda, Zainal Abidin; Nabila, Abdul Malek (EDP Sciences, 2018)
The concept of learning while playing to learn language is a pedagogy that can enhance students’ learning interest. In this digital era, the use of board games, for instance, has provided a solution to learning a language. A considerable literature has grown up around the theme of digital board in language learning. Therefore, this paper aims at finding the significance of developing a digital board game for the purpose of vocabulary learning. Fifty-seven (57) students from Universiti Malaysia Pahang (UMP) were selected as samples using purposive random sampling to collect data for the current study. A questionnaire was employed to explore their needs of a digital board game to learn vocabulary. The findings revealed that digital board game has significant needs among students to learn vocabulary, and further support the idea of using digital board game in language classroom. Majority of them believed that digital board game may provide a significant impact on vocabulary learning. Overall, the current study proves to be particularly valuable to language teachers to incorporate digital board game into their instructional activity. Also, these findings suggest a role for interactive learning in motivating language learner to enrich their vocabulary size